(3eNJUQ aj JYHjQ GdQDjGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3eNJUQ ai JYHjQ GdQDjG dGHf SjfG hGJab Ydi UMjI LejY GdeYJHQjf Yf GdKbGJ s
(3BNQgG (B:s
(3dGjOd Ydi TZd GdbdH ef CaYGdg jOd Ydi cKQI GdWGYI dg hGddg CYde HGdUhGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdOcJhQ MSjf Ydi eMahX (B_ (3HZOGO (B(96) s
Keywords: (3JYHjQ GdQDjGs